A proposed terminology for the dentition of gomphodont cynodonts and dental morphology in Diademodontidae and Trirachodontidae - Hendrickx, Christophe (2019)
Gomphodont cynodonts were close relatives of mammals and one of the Mesozoic lineages of cynodont therapsids that became extinct at the end of the Triassic. Gomphodonts were omnivorous to herbivorous animals characterized by labiolingually expanded postcanines, which allowed tooth-To-Tooth occlusion. The morphology of the upper and lower postcanines presents important means of distinguishing among major lineages within Gomphodontia, that is, Diademodontidae, Trirachodontidae, and Traversodontidae, but the dentition of most Diademodontidae and Trirachodontidae remain poorly documented. Here, we present a comprehensive description of the dentition of each diademodontid and trirachodontid species, as well as detailed illustrations of each dental unit, after firsthand examination of material and 3D reconstructions of postcanine teeth. Based on dental morphology, Trirachodon berryi and "Trirachodon kannemeyeri," considered as separate taxa by some authors are here interpreted as representing different ontogenetic stages of the same species. Likewise, Sinognathus and Beishanodon, thought to belong to non-cynognathian cynodonts and traversodontids by some authors, are referred to Trirachodontidae and Gomphodontia based on dental characters, respectively. Finally, we propose a standardized list of terms and abbreviations for incisors, canines, and postcanines anatomical entities, with the goal of facilitating future descriptions and communication between researchers studying the gomphodont dentition. Subjects Evolutionary Studies, Paleontology.